Fungal ectoparasites increase winter mortality of ladybird hosts despite limited effects on their immune system - Knapp, Michal; Řeřicha, Michal; Haelewaters, Danny; González, Ezequiel (Proceedings. Biological sciences, 2022)
Winter represents a challenging period for insects inhabiting temperate regions. A plethora of studies have investigated how environmental conditions such as temperature affect insect overwintering success. However, only a few studies have focused on biotic factors and the mechanisms affecting the overwintering performance of insects. Here, we investigated the effects of the parasitic fungus Hesperomyces virescens on the overwintering performance and immune system functioning of the invasive ladybird Harmonia axyridis. Winter survival was significantly lower for infected than for uninfected ladybirds. Body mass loss during overwintering tends to be higher for infected individuals compared to uninfected ones and for larger ladybirds. In addition, parasitic infection reduced post-winter longevity without food in male but not female ladybirds. Total haemocyte and protein concentration as well as antimicrobial activity against Escherichia coli significantly decreased during ladybird overwintering. However, haemolymph parameters were only poorly affected by Hesperomyces infection, with the exception of antimicrobial activity against E. coli that tended to be higher in infected ladybirds. Interestingly, none of the pre-winter haemolymph parameters were good predictors of ladybird winter survival. Overall, our results indicate that energy exhaustion unrelated to immune system challenge is the most probable explanation for increased overwintering mortality in infected ladybirds.
Keywords: stress resistance; pathogen; Humans; hmyz; body condition; imunitní systém; Anti-Infective Agents; Escherichia coli; Immune System; antiinfekční látky; ecophysiology; lidé; zvířata; Coleoptera; Insecta; sexually transmitted diseases; roční období; Male; Seasons; microsporidia load; brouci; Animals; mužské pohlaví